The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fncel.2018.00052
|View full text |Cite
|
Sign up to set email alerts
|

Histological Characterization of the Irritative Zones in Focal Cortical Dysplasia Using a Preclinical Rat Model

Abstract: Current clinical practice in focal epilepsy involves brain source imaging (BSI) to localize brain areas where from interictal epileptiform discharges (IEDs) emerge. These areas, named irritative zones, have been useful to define candidate seizures-onset zones during pre-surgical workup. Since human histological data are mostly available from final resected zones, systematic studies characterizing pathophysiological mechanisms and abnormal molecular/cellular substrates in irritative zones—independent of them be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Activation of NMDAR allows the influx of sodium ions and the outflow of potassium ions, which ensures depolarization of the neuronal membrane. It has been shown that in foci of focal cortical dysplasia characterized by high epileptogenicity, NMDAR expression increases [60]. In addition, pathological activation of NMDAR leads to hyperexcitation and increased activity of neurons, which is the pathophysiological basis for epileptogenesis [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NMDAR allows the influx of sodium ions and the outflow of potassium ions, which ensures depolarization of the neuronal membrane. It has been shown that in foci of focal cortical dysplasia characterized by high epileptogenicity, NMDAR expression increases [60]. In addition, pathological activation of NMDAR leads to hyperexcitation and increased activity of neurons, which is the pathophysiological basis for epileptogenesis [61,62].…”
Section: Discussionmentioning
confidence: 99%
“…The pilocarpine model was used to induce temporal lobe epilepsy in rats of approximately 4 weeks of age, using a procedure similar to that carried out previously in ref and . Upon reaching a state of spontaneously recurring seizures, one of the subject rats was used for the in vivo experiments.…”
Section: Methodsmentioning
confidence: 99%
“…In human resected tissues, the N1R immunoreactivity of dysplastic and dysmorphic neurons was increased; moreover, NR2A and NR2B were also overexpressed, which is a feature of hyperexcitable developing neurons [21,23]. In CD animal models, NR2B and NR1 were also upregulated in lesions [17,24]. Furthermore, in vitro ifenprodil reduced the excitability of CD brain tissue slices, and in vivo administration of ifenprodil blocked NR2B; these results clari ed the important roles of NR2B and NR1 upregulation in increasing epileptogenicity in the rat frozen model of CD [25,26].…”
Section: Abnormal Excitation In CDmentioning
confidence: 99%
“…The intensity and frequency distribution of EEG was obtained from the power spectrum by fast Fourier transform with a 2-s Hanning window across a continuous 1-500 Hz frequency range. The absolute power (μV2) of each EEG frequency band [delta (1)(2)(3)(4) Hz), theta (4-8 Hz), alpha (8-13 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), lower gamma (30-60 Hz), higher gamma (60-80 Hz), ripple (80-250 Hz) and fast ripple (250-500 Hz)] at selected pre-pilocarpine resting periods (background activity) and post-pilocarpine ictal periods were compared between the rHMGB1-treatment rats and the control rats. Time-frequency and wavelet analyses were performed using Morlet wavelets in Brainstorm, which was developed with MATLAB software.…”
Section: Eeg Acquisition and Analysismentioning
confidence: 99%